Measuring the underlying causes of long waiting times and the barriers to implementing recommendations to reduce waiting times, at a public sector primary health care facility in Cape Town - Caesar, Warren (University of the Western Cape, 2019)
Magister Commercii (Information Management) - MCom(IM) === Long waiting times before receiving a health service, give rise to long queues and congested health facilities, both of which are unnecessary and avoidable. Since patients in part judge the quality of the service by the length of time they spent waiting for it, it is imperative to measure waiting times, and determine and mitigate the immediate and underlying causes of lengthy waits. The facility under investigation was known to have excessively long waiting times. Since the immediate causes of long waiting times were known, it was thus required to research and understand the underlying causes of long waiting times and consequently whether there were any barriers to implementing recommendations to reduce waiting times at this primary health care facility. Aim: The aim of the study was to determine the underlying causes of long waiting times and the barriers to implementing recommendations to reduce waiting times. Methods: A quantitative cross-sectional analytical study with a small qualitative component was undertaken. The qualitative study took a workshop format by piggy-backing onto feedback sessions held to present the results of the previously conducted waiting time survey to staff. Staff commentary at the workshops on possible underlying causes and barriers to recommendations to reduce them, were then used to develop a questionnaire for the quantitative portion of the study. The population and sample for the qualitative part of the study were all staff working at the facility who attended the feedback sessions. The cross-sectional descriptive quantitative study intended to uncover what underlying causes affected long waiting times, what recommendations could be explored to mitigate long waiting times and improve the patient experience, and if there were any barriers to these recommendations. The quantitative study population and sample were all staff who worked at the facility for more than six months and all patients who had utilised the services at the facility for three or more times. Data was collected using structured questionnaires, which were different for staff and patients. A detailed descriptive analysis was conducted. Results: The study found a number of potential underlying causes for each immediate cause of long waiting times at the facility. For early morning batching the underlying causes found were: 45% of patients were given early appointments which caused clients to arrive early; 100% of patients with appointments after 10H00 arrived before 10H00; and 43% of the patients stated that they arrived early because they feared being turned away.